Protagonist’s Self-writing in French Novel: Approaching the Problem of Genre Paradigm - Pavlenko, Yulia (Pitannâ lìteraturoznavstva, 2013)
The article introduces the analysis of the French novel’s genre parameters, one of the core element of which is the specificity of the narrative form of a protagonist-narrator’s self-writing. The given research is based on J.-M. Schaeffer’s ideas (Qu’est-ce qu’un genre littéraire?). It focuses on the communicative frame of writing’s space about one(him/her)self. The study shows that the text’s convention with “Self-writing” genre is of great importance. Analytical description of the structural characteristics as methodological approach to the novels, in which poetic landscape is Self-writing by fictional person, identifies genre indexes, characteristics and markers of writing about oneself. As a result, the study makes it possible to assert the existence of transhistorical constants in such type of novels from the period of Enlightenment to the literary modernism times. Connection between genre indexes and characteristics serves one more object of the analysis. The study introduces the category of self-writing “indirect” index, which changes the structure of the genre expectations and transforms genre into paragenre. A special attention in the field of interpretation is paid to the correlation of fiction and reality in self-writing. The study comes to the definition of self-writing genre’s intentionality. A protagonist, who performs the function of homo scribens, enters into a dialogue with Self-Other, with an eye to disclosure innner secrets of his world and to achieve the self-harmonization, resulting in, accordingly, a change of the trajectory of his future through understanding of the past.